Disaggregating The Agency Contract: The Effects Of Monitoring, Incentive Alignment, And Term In Office On Agent Decision Making - Tosi, Henry L.; Katz, Jeffrey P.; Gómez‐Mejía, Luis R. (Academy of Management Journal, 1997)
Using a laboratory design, we examined the simple and interactive effects of monitoring and incentive alignment on managerial decisions. Length of term in office was a third independent variable. Results show that incentive alignment was a more powerful mechanism than monitoring for ensuring that agents acted in the interests of owners. An interaction of monitoring, incentive alignment, and term in office revealed that these effects are relatively complicated and deserve further study. Also, incentive alignment had a beneficial effect for the principal for long-term CEOs, even though the tendency to escalate (an effect negative for principals) was greatest for those agents.